2018
DOI: 10.5937/industrija46-16696
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental drivers of prosperity in the European Union and Western Balkans countries

Abstract: In this paper the aim is to identify key drivers that have contributed the most to the prosperity of European Union and Western Balkan countries in the 2007-2016 period. Empirical analysis is based on data for cumulative growth rate of values of nine original Legatum Prosperity Index (LPI) pillars and on implementation of Multivariate Data Analysis. Using Principal Component Analysis, four principal components are obtained and we named them: Economic Environment, Social Infrastructure, Institutional Framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This view also has empirical support. Previous studies have found that the low quality of institutional framework in Western Balkans transitional countries negatively affects the prosperity of these countries (Jovanović Gavrilović and Gligorić, 2018). Not in the least because of this reason, we are interested in exploring the fragility of the type of moral capital that corresponds to morally elevated interactions, such as judged based on a Christian set of values.…”
Section: Production Function Output (Y)mentioning
confidence: 99%
“…This view also has empirical support. Previous studies have found that the low quality of institutional framework in Western Balkans transitional countries negatively affects the prosperity of these countries (Jovanović Gavrilović and Gligorić, 2018). Not in the least because of this reason, we are interested in exploring the fragility of the type of moral capital that corresponds to morally elevated interactions, such as judged based on a Christian set of values.…”
Section: Production Function Output (Y)mentioning
confidence: 99%